Unscrambling the egg: reform pathways in the tax transfer system - Hodgson, Helen (Taxation Institute of Australia, 2011)
Since 1985 the interaction of the tax transfer system has been reviewed a number of times. This was again a key term of reference of the Henry Review 1. A review of the evolution of the personal income tax transfer system between 1985 and 2007 shows clear trends in rates and entitlements: benefits have become targeted rather than universal; tax rate structures have simplified and flattened; and pension entitlements are now subordinated to superannuation requirements. Recent criticism of the Henry Review has proposed returning to more progressive income tax rates and universal benefits in relation to family benefits in particular 2. This proposal is based on economic modelling as to the impact of the current tax transfer system and the effect that the current structure has on two earner families. However it does not have regard to institutional pathways that have been influential in shaping the current system. Institutional theory recognises that successful change in political institutions depends on previous systems and attitudes to further change. In this paper I will examine the argument that the return to universal benefits will make the system more progressive, comparing the pre 1985 system with the current system. I will then consider the role of universal benefits in a welfare system before applying institutional theory to explore the implications of returning to the system of family benefits that was in place in 1985. Finally I will trace the institutional pathway of changes to the family benefit system in Australia since 1985, with reference to shifts in the progressivity of the tax transfer system and the effect of change on workforce participation.